The Effect of Grammatical Understanding on the Ability of Writing Thesis Students - Rati - Riana; Susanto Susanto (Fakultas Ilmu Pendidikan dan Humaniora (FIPH), Universitas Muhammadiyah Semarang, 2022)
The purpose of this research is to decrypt and analyze whether grammatical understanding affects the writing ability of Semarang University’s students thesis and how it affects. This type of research is quantitative research with the type of research is inference used to test hypotheses to determine the influence of grammatical understanding on the ability to write thesis. The sample of this study was students who were preparing the thesis of four courses that were taken randomly. Sampling techniques using probability sampling. Data collection techniques are carried out by direct observation using structured questionnaires. Quantitative data of questionnaire results tested with F-test. While qualitative data from thesis text analysis is analyzed descriptively. The result is that between right and wrong in 10 criteria of grammatically, that is 57.43% true and 42.57% wrong. Based on the F-test results obtained results that the regression coefficient of 0.672 with a significance value of 0.000 < 0.05. This means that the effectiveness of sentences has a positive and significant influence on grammatical understanding in writing thesis. This influence supports the analysis of thesis documents with the findings of 636 sentences from the thesis author. Of the 636 sentences found 429 sentences were grammatical and 207 sentences were not grammatical. The ungrammatically of the sentence is caused by several things, namely sentences without a subject, without predicates, without predicates and predicates, double-substitutes, double predicates, objects preceded by forejectives, substitutes and double-predicates, repeating subjects, without objects, not using the conjunction ”bahwa”, and inaccuracies in the use of hyphens ”then”.